Perceived Organisational Justice and Climate on Counterproductive Work Behaviour among Public Employees - Madzivhandila, Rofhiwa; Babalola, Sunday Samson; Khashane, Khathutshelo (Journal of Reviews on Global Economics, 2019)
Employee work activities that are more than expectations are the panacea for organisational success, in today’s dynamic workplace. In achieving this set goal, organisations need to be seen, by employees as taking care of their welfare, as employees are significant resources of an organisation. This study investigated perceived organisational justice and climate on counterproductive work behaviour (CWB) among public employees. A quantitative research design was used, with self-administered questionnaires for the collection of data. Three hundred and seventy-seven employees from public service organisations participated in the study. The participants were made up of 183 (50.3%) females, with a mean of 35.41 years of age, and 7.42 years of working experience. Results revealed that organisational justice and CWB were statistically significant (F (1, 359) = 11.53, p < 05). It was also found that organisational climate and CWB were statistically significant (F 1, 359) = 18.94, p < 0.05). The findings were discussed in line with the literature, as well as outlining their implications for management and suggesting appropriate recommendation. Specifically, the study suggested the creation of an enabling environment that will ensure that employees are well treated; this will encourage employees to take calculated risks with the aim of advancing the organisational objectives, promote employee citizenship behaviour as well as reduce dysfunctional behaviour.